Edukasi Pemilahan Sampah dan Pemanfaatan Barang Bekas sebagai Tempat Sampah di Desa Sukorejo - Hidayat; Sutrisno Adi Prayitno; Rohmat; Atikah Aulia Dina (PT. Gyandharma Global Media, 2026)
Waste management remains an environmental challenge faced by communities in both urban and rural areas. Low public awareness in sorting and disposing of waste properly causes environmental cleanliness problems, unhealthy conditions, and potential pollution. This community service activity aimed to improve community knowledge regarding the importance of sorting organic and inorganic waste and to encourage the utilization of used goods as trash bins. The activity was carried out in Sukorejo Village, Sidayu District, Gresik Regency, with PKK women as the main target group. The methods used were counseling, demonstration, and direct practice. The implementation stages included preparation, execution, and evaluation. The results showed high community enthusiasm in participating in the socialization and practice of making trash bins from used paint buckets. The outputs of the activity were 14 trash bins consisting of 7 organic and 7 inorganic bins distributed to several public points in Sukorejo Village. This activity had a positive impact on increasing community understanding of waste management while supporting the creation of a cleaner and healthier environment.